Banknotes as Matter and as the Support for Semiosis: Towards a Semiotics of Paper Money - Moreno, Sebastián (E|C, 2023)
Nowadays, banknotes and coins are part of an economic system that over time has become more digital, complex and diversified. These two elements are created in different material supports: while coins are minted in metal, banknotes are designed in a type of paper called paper money. Although its use is decreasing, we normally use(d) paper money in our daily lives to resolve economic exchanges. This article approaches paper money from a semiotic perspective and regards it a material that has some features that make it an appropriate medium to convey social meaning through visual language. Besides its economic function, paper money also serves the State to convey contents linked to national identity and cultural memory. After approaching paper money as an element and studying some of its material characteristics, the article focuses on studying it as the support for semiosis and of how States use banknotes to convey meanings related to national identity and cultural memory.